?DEVELOPMENT OF BIMETAL TEST SPECIMEN FOR TESTING MATERIALS AT HIGH HOMOLOGOUS TEMPERATURE (Biological Sciences - PJSIR, 1995)
A bimetal test specimen has been developed to be used for testing materials at high homologous temperatures. The testing material selected is 50/50 lead-tis solder. At room temperature its homologous temperature is 0.6. Specimen manufacturing method adopted is simple and economical. OFHC copper has been used as a rigid support to install extensometer for strain measurements and to hold the specimen by the testing machine grips. Copper has been used because it provides a strong bond with solder and it is easy to manufacture copper to the required shape and size. The strain produced in the copper is 123 times less than that produced in solder.Formula has been devel- oped to calculate the strain produced in the gage section using the strain value measured using extensometer in- stalled on copper.